Green human resource management - whether and how can human resource management support a company’s eco-efficiency ? - Urbaniak, Bogusława (W poszukiwaniu zielonego ładu, 2022)
Green HRM (GHRM) plays an intermediary role between employees and managers, working together to achieve the company’s strategic objectives while respecting the principles of the green economy. It refers to the HR function, which is distinguished by its ecological aspect in line with other aspects of sustainable development ̶ economic and social. The chapter focuses on the benefits that the company achieves thanks to GHRM. The main areas of GHRM and how to build green competences are presented.